Analysis of BPHTB Collection Obstacles in Land Rights Registration at ATR/BPN Bandar Lampung - Syafiqo Naila Putri; Ratna Septiyanti (LPPM STIE Krakatau, 2026)
Purpose: This study aims to analyze the implementation of the Land and Building Acquisition Duty (BPHTB) collection, identify the problems encountered, and examine the strategies undertaken to address these issues in Bandar Lampung. Methodology: This study employed a qualitative approach with descriptive characteristics. Data were collected through interviews, observations, and document analysis. The collected data were analyzed using the data reduction, data presentation, and conclusion-drawing stages. Results: The findings show that the BPHTB collection at the Ministry of ATR/BPN generally complies with existing regulations. However, challenges remain, including low taxpayer compliance, limited comparative data, discrepancies between the NJOP and market value, and limited human resources for verification. The proposed solutions include stronger supervision, improved information systems, and broader public socialization. Conclusions: Although the BPHTB collection has been implemented according to the applicable provisions, its effectiveness remains limited by administrative and technical challenges. Stronger institutional coordination and system improvements are required to optimize the collection process. Limitations: This study is limited to the BPHTB collection process in Bandar Lampung and focuses primarily on qualitative findings, which may limit the generalizability of the results to other regions. Contribution: This study contributes to the understanding of BPHTB collection practices by identifying practical obstacles and proposing strategic improvements that may support more effective tax administration and local revenue management.